“I Think It’s Too Early to Know”: Gender Identity Labels and Gender Expression of Young Children With Nonbinary or Binary Transgender Parents - Riskind, Rachel G.; Tornello, Samantha L. (Frontiers in Psychology, 2022)
Little is known about gender expression among children with transgender and nonbinary (TGNB) parents. We conducted a web-based survey of 64 predominantly White TGNB parents in the U.S.; their children were 18 to 71 months of age. Many participants, particularly those with younger children, declined to label their child’s gender identity. Scores indicated that, on average, children’s play was conventionally gendered. However, scores indicated significantly more gender-expansive play in the present sample than in normed samples, particularly among children assigned male at birth. Findings support transfamily theory (McGuire et al., 2016) and illustrate differences among families with TGNB parents.